2015
DOI: 10.1007/s00044-015-1425-6
|View full text |Cite
|
Sign up to set email alerts
|

Activity-guided isolation and identification of the major antioxidant and anticancer compounds from a commercial Pelargonium sidoides tincture

Abstract: Extracts prepared from the roots of Pelargonium sidoides (DC) are commercially available for the treatment of respiratory related conditions. Recently, a commercial radix mother tincture of this plant was shown to have both antioxidant and anticancer effects especially related to the G 0 /G 1 block in the Jurkat E6.1 cell line (unpublished results). Fractions were prepared by semi-preparative HPLC, and their antioxidant and anticancer activities were determined. The more hydrophilic fractions isolated namely F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…The characteristic fragmentation pathways for PACN are the quinone methide mechanism, heterocyclic ring fission, and retro-Diels-Alder (RDA) fission with neutral losses of 168 Da [ 24 ]. These compounds produced m / z ions of 609, 913, 1217, 1521, 1825, respectively, with various fragment ions ( Table 1 ) obtained by the loss of a galloyl and RDA fragments [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic fragmentation pathways for PACN are the quinone methide mechanism, heterocyclic ring fission, and retro-Diels-Alder (RDA) fission with neutral losses of 168 Da [ 24 ]. These compounds produced m / z ions of 609, 913, 1217, 1521, 1825, respectively, with various fragment ions ( Table 1 ) obtained by the loss of a galloyl and RDA fragments [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 The cell signaling pathways identified here are also under oxidative control as has been observed with the PI3K-Akt and the Janus Kinase (JAK)-signal transducers and activators of transcription protein (STAT) signaling pathways as well as the Src protein kinases that can then go on to activate the PI3K-Akt, Ras/Raf/MAPK and STAT pathways [62][63][64][65][66][67]. The bioactive compounds identified from P. sidoides were also shown to have significant antioxidant activity in vitro [17]. Thus, P. sidoides besides regulating these signal transduction pathways through possible direct interaction with the concerned protein kinases, may also regulate these same pathways by scavenging the reactive oxygen and nitrogen species that can also activate these pathways.…”
Section: Protein Interaction Network and Pathway Enrichment Analysismentioning
confidence: 59%
“…In previous studies, we found anti-proliferative activity for a commercial radix mother tincture of P. sidoides in vitro and through a bioactivity-guided approach; we isolated seven fractions with significant anti-proliferative activity [17,18]. Liquid chromatography with tandem mass spectrometry detection (LC-MS/MS) analysis of these fractions revealed the presence of phenolic compounds gallic acid, koaburaside, proanthocyanidin dimers as well as a trimer, dihydroxycoumarin sulfates, trihydroxycoumarin as well as three turgorins namely leaf movement factor (LMF) 2, LMF3 and the periodic leaf movement factor 1 (PLMF1).…”
Section: Introductionmentioning
confidence: 88%
“…Geranium essential oils are known to exhibit anti-cancer activity [21,22]. Previous studies have shown that the Pelargonium species have cytotoxic activity on cancer cells [2,7,23].…”
Section: Iscussionmentioning
confidence: 99%
“…Although a considerable amount of research has been performed on the biological activities of the Pelargonium species, knowledge on its anticancer activity is limited. Data on this subject suggest that fractions of P. sidoides have anti-growth effects on the Jurkat E6.1 human leukemic T cell lymphoblast cell line [7], while another study reported that P. zonale extract had minimal cytotoxicity against the HeLa cell line [2].…”
Section: Introductionmentioning
confidence: 98%